Organizational Aesthetics: Caught Between Identity Regulation and Culture Jamming - Wasserman, Varda; Frenkel, Michal (Organization Science, 2011)
Applying insights from Lefebvre's spatial theory [Lefebvre, H. 1991. The Production of Space. Blackwell, Oxford, UK] to an analysis of Israel's Ministry of Foreign Affairs—recently relocated to its new award-winning building—the present study seeks to offer a more comprehensive model of the role of organizational aesthetics (OA) in identity regulation and culture jamming. Our contribution is threefold. (1) At the empirical/methodological level, this study attempts to simultaneously analyze the three Lefebvrian spaces in a single organization, demonstrating negotiations and struggles over interpretations of OA. (2) We analyze aesthetic jamming as a form of intentional and unintentional efforts at collective resistance that not only reveals the aesthetic mechanisms of regulation, but actually uses them as a method of counter-regulation. (3) Whereas most studies in this emerging body of literature focus on the regulation of organization-based identities (bureaucratic and professional), we show how the translation of extraorganizational hierarchies of identities (national, ethnic, and gendered) into the organizational control system is also mediated by OA.